1973
DOI: 10.1128/jb.115.3.987-991.1973
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutases of Escherichia coli : Intracellular Localization and Functions

Abstract: Escherichia coli B contains two superoxide dismutases which differ with respect to their localization within the cell, the nature of their prosthetic metals, their responses to changes in p02, and their functions. One of these enzymes, which was liberated from the cells by osmotic shock and which was therefore presumed to be localized in the periplasmic space, is an iron-containing superoxide dismutase. The amount of this iron enzyme did not vary in response to changes in p°2 during growth. In contrast, the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

1974
1974
2012
2012

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(47 citation statements)
references
References 12 publications
1
42
0
2
Order By: Relevance
“…Cells of Escherichia coli grown under 100% O2 were much more resistant to hyperbaric O2 than cells grown under air, but this was not true for Bacillus subtilis (Gregory and Fridovich, 1973b). Cells of Escherichia coli B depleted of periplasmic superoxide dismutase by growth on an iron-deficient medium were much more rapidly killed by 02" than normal cells (Gregory et al, 1973). Mutants of E. coli temperature-sensitive in superoxide dismutase activity show a comparable defect in their ability to grow in O2 (Gregory and Fridovich, 1974).…”
Section: Superoxide Dismutasementioning
confidence: 97%
See 2 more Smart Citations
“…Cells of Escherichia coli grown under 100% O2 were much more resistant to hyperbaric O2 than cells grown under air, but this was not true for Bacillus subtilis (Gregory and Fridovich, 1973b). Cells of Escherichia coli B depleted of periplasmic superoxide dismutase by growth on an iron-deficient medium were much more rapidly killed by 02" than normal cells (Gregory et al, 1973). Mutants of E. coli temperature-sensitive in superoxide dismutase activity show a comparable defect in their ability to grow in O2 (Gregory and Fridovich, 1974).…”
Section: Superoxide Dismutasementioning
confidence: 97%
“…E.xposure of membranes to a source of O2~ causes peroxidation. Bacteria and viruses exposed to 02~ are rapidly killed (Lavalle, Michelson and Dimitrijevic, 1973;Gregory, Yost and Fridovich, 1973;Gregory and Fridovich, 1974). Production of Oj" may be responsible for the effects of bipyridyl herbicides (Farrington et aL, 1973) and for the nerve degeneration caused by injecting animals with 6-hydroxy-dopamine (Heikkila and Cohen, 1973).…”
Section: +-0h+02mentioning
confidence: 99%
See 1 more Smart Citation
“…Mandell has reported that neutmphils killed a low-catalase strain of S. aureus better than a high-catalase strain (23). On the other hand, Gregory et al found that induction of increased concentrations of SOD in Escherichia coli by growth in oxygenated medium protected bacteria against endogenous 02-resulting from further increases in pO2, but offered no protection against exogenous 02-generated by photochemical or xanthine oxidase systems (24). In experiments reported here, neither species of candida scavenged H202 or 02-derived from chemical sources or macrophages, and C. albicans was killed at least as easily as C. parapsilosis by exogenously generated oxygen radicals.…”
Section: Parapsilosismentioning
confidence: 99%
“…Proteins consisting of the N-terminal 59 amino acids of E. coli SodA or SodB fused to PhoA were both exported to the periplasm, although both proteins are considered cytoplasmic in E. coli (Britton and Fridovich, 1977;Serres et al, 2004). Interestingly, E. coli SodB was originally described as a periplasmic protein (Gregory et al, 1973) and export of an E. coli SodB-PhoA fusion protein was also previously reported by Bailey and Manoil (2002). Possibly this is an indication that while E. coli SodA and SodB are targeting-competent, these proteins are only exported under certain conditions, and remain within the cytoplasm under standard laboratory conditions.…”
Section: Soda Export Is Regulatedmentioning
confidence: 99%